Au croisement des temporalités et des processus post-catastrophe : Canaan et le camp Corail - Astrid Lenoir (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In Haiti, following the earthquake of January 12, 2010, a sparsely populated territory located in the north of Port-au-Prince was selected for the construction of Camp Corail. This temporary housing camp, divided in two sectors, enabled the relocation of around 10,000 people. The area surrounding Canaan quickly became a real residential district, with the spontaneous settlement of tens of thousands of people. Gathered on the same territory, we explore the way in which these two entities were constituted (the Camp Corail and Canaan) through the analysis of the role, practices, discourses and representations of different actors.